Enhanced antioxidant activity and in vitro release of propolis by acid-induced aggregation using heat-denatured zein and carboxymethyl chitosan. (August 2018) - Zhang, Hao; Fu, Yuying; Niu, Fuge; Li, Zeya; Ba, Chujie; Jin, Bing; Chen, Guowen; Li, Xiaomeng
Abstract: Propolis is a natural resinous mixture from many plant materials, buds, and exudates and is rich in polyphenols with several health beneficial properties. However, its application in food products and pharmaceuticals is hindered because of its low water solubility, undesirable sensorial characteristics and limited bio-accessibility. Here, we originally report the design and synthesis of food-grade colloidal nanoparticles as propolis carriers to enhance its oral bioavailability. Propolis was encapsulated into heat-denatured zein with carboxymethyl chitosan (CMCS) coating by acid-induced aggregation. Calcium cross-linking provided the best controlled release of propolis and improved encapsulation efficiency. The complex nanoparticles prepared under optimized conditions were spherical in shape with a Z-average diameter of ∼156 nm and zeta potential of ∼ -30 mV. Encapsulation efficiency (EE) and loading content (LC) of propolis in heat-denatured zein/CMCS nanoparticles reached∼83% and∼13.83%, respectively. Fourier transform infrared (FTIR) indicated that hydrogen bonds, electrostatic and hydrophobic interactions were the major forces responsible for nanoparticle formation. The in vitro antioxidant activity of propolis encapsulated in nanoparticles was considerably stronger than that of propolis dispersed in water. This new approach of fabricating propolis-loaded heat-denatured zein/CMCS nanoparticle provides a promising strategy with high yield and is non-toxic with improved water solubility, antioxidant activity and sustained release of propolis. Graphical abstract: Image 1 Highlights: ● Propolis nanoparticles were formed with Heat-denatured zein and CMCS (Z/CMCS NPs). ● Z/CMCS NPs were fabricated by acid-induced aggregation and calcium cross-linking. ● Nanoparticles formed by hydrogen bonds, electrostatic and hydrophobic interaction. ● Nanoparticulated propolis showed controlled release behavior. ● Nanoparticulated propolis showed improved in vitro antioxidant activity.